Employability of Teacher Education Graduates under CMO 75, s.2017: Assessing Employers’ Feedback and Level of Satisfaction - Mangundayao, Jessie Ray; Hernandez, Genelita (International Journal of Sustainability and Advanced Integrated Research, 2026)
One critical measure of success in workplaces is an employees’ ability to use competently the knowledge, skills and values that meet the needs of his job, satisfy the demands of the employer, and contribute to the overall achievement of institutional goals. The paper seeks to describe the employability of the graduates of Mindoro State University in consonance with the CMO 75, s.2017. The research utilized descriptive research design. The questionnaire enables the employers to express their feedback and satisfaction on the five areas of employability enumerated as professionalism and work ethic, communication and collaboration, critical thinking and problem solving, adaptability and flexibility, technological savvy and digital literacy. The research findings underline the graduates’ commendable performance in demonstrating professionalism and work ethic, a vital aspect for success in the teaching profession. Additionally, the graduates exhibit strong communication and collaboration skills, an essential competency for educators who need to engage with colleagues, superiors, and stakeholders effectively. However, the feedback indicates room for growth in conflict resolution and creative problem-solving within collaborative settings. While the graduates excel in adaptability and flexibility, their aptitude in using technology, although strong, could be enhanced. Furthermore, the graduates’ demonstrated strengths in critical thinking and problem-solving are accompanied by a readiness to embrace new challenges. Research’s holistic evaluation of graduates’ attributes showcases their preparedness for the demands of the educational sector. While the strengths are evident, tailored interventions to address areas of growth, like conflict resolution, creative problem-solving, and technology integration, can contribute to well-rounded and adaptable educators.